Problematika Yuridis Wakaf Hak Kekayaan Intelektual di Indonesia - Eva Mir'atun Niswah (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2018)
Intellectual Property Rights (IPR) is one of movable objects that can be represented according to waqf regulation (Undang-Undang No. 41 Tahun 2004 Tentang Wakaf). The previous regulations did not mention IPR as waqf object. IPR becomes waqf object because there is a shift of paradigm on productive waqf. However, the waqf regulation (Undang-Undang No. 41 Tahun 2004 Tentang Wakaf) has many juridical problems. For example, there is no specific explanation about IPR waqf as well as money waqf. Besides, the IPR practice is very rare due to unclear forms of IPR waqf. Juridical problems on IPR waqf are related to legal substance, legal structure and legal culture. On legal substance, there is no clear explanation and mechanism of IPR waqf. On legal structure, there is no clear explanations about who can be the wakif or nazir on IPR waqf. On legal culture, many people are still unfamiliar with intangible waqf object (the conventional waqf object is land). Therefore, the acceptance of an intangible object such as IPR as a waqf object is very low.